Energy Metabolism and Redox State in Brains of Wistar Audiogenic Rats, a Genetic Model of Epilepsy - Dechandt, Carlos Roberto Porto; Ferrari, Gustavo Duarte; dos Santos, Jonathas Rodrigo; de Oliveira, José Antonio Cortes; Silva-Jr, Rui Milton Patrício da; Cunha, Alexandra Olimpio Siqueira; Garcia-Cairasco, Norberto; Alberici, Luciane Carla (Frontiers in Neurology, 2019)
The Wistar Audiogenic Rat (WAR) strain is a genetic model of epilepsy, specifically brainstem-dependent tonic-clonic seizures, triggered by acute auditory stimulation. Chronic audiogenic seizures (audiogenic kindling) mimic temporal lobe epilepsy, with significant participation of hippocampus, amygdala and cortex. The objective of the present study was to characterize the mitochondrial energy metabolism in hippocampus and cortex of WAR and verify its relationship with seizure severity. Hippocampus of WAR naïve (no seizures) presented higher oxygen consumption in respiratory states related to the maximum capacities of phosphorylation and electron transfer system, elevated mitochondrial density, lower GSH/GSSG and catalase activity, higher protein carbonyl and lactate contents, than their Wistar counterparts. Audiogenic kindling had no adding functional effect in WAR, but in Wistar it induced the same alterations observed in the audiogenic strain. In the cortex, WAR naïve presented elevated mitochondrial density, lower GSH/GSSG and catalase activity, and higher protein carbonyl. Chronic acoustic stimulation in Wistar induced the same alterations in cortex and hippocampus. Mainly in the hippocampus, WAR naïve presented elevated mRNA expression of glucose, lactate and excitatory amino acids transporters, several glycolytic enzymes, lactate dehydrogenase and Na+/K+ ATPase in neurons and in astrocytes. In vivo treatment with mitochondrial uncoupler 2,4-dinitrophenol (DNP) or N-acetylcysteine (NAC) in WAR had no effect on mitochondrial metabolism, while lowered oxidative stress. Unlike DNP, NAC downregulated all enzyme genes involved in glucose and lactate uptake and metabolism in neurons and astrocytes. Additionally, it was able to reduce brainstem seizure severity in WAR. In conclusion, in WAR naïve animals both cerebral cortex and hippocampus display elevated mitochondrial density and/or activity associated with oxidative damage, glucose and lactate metabolism pathways upregulation, and increased Na+/K+ ATPase mRNA expression. Only in vivo treatment with NAC was able to reduce seizure severity of kindled WARs, possibly via down regulation of glucose/lactate metabolism. Taken together, our results are a clear contribution to the field of mitochondrial metabolism associated to epileptic seizures.